Efisiensi Penggunaan Input pada Budidaya Keramba Jaring Tancap di Kecamatan Nambo Kota Kendari - Fitriah Amir; Budiyanto Budiyanto; La Ode Alwi (Jurnal Sosio Agribisnis, 2021)
The aim of this study is to analyze of input affected the This study aims to analyze the effect of inputs on production, and to analyze the allocative efficiency of input use in the fence net cages farming. The study was conducted in Nambo District, Kendari City, from April 2020 to June 2021. The population in this study were farmers of fence net cages. The sample was determined using simple random sampling technique. The number of samples selected as many as 64 respondents. Data was analyzed using multiple non-linear regression and allocative efficiency. The results showed that together, the number of seeds, the amount of shrimp head feed, the amount of trash fish feed, the number of labours and the area of the cage had an significant effect on the production of fence net cages farming. Partially, only the number of seeds and trash fish feed had a significant effect, while the amount of shrimp head feed, labors and cage area had no significant effect. The amount of seed and trash fish feed that is used allocatively is not efficient, so it needs to be increased its use. While the use of the amount of shrimp head feed, labor and cage area allocatively is not efficient Keywords: allocative efficiency; production inputs; fence net cages